The death of the merchant. A window onto Business in the Indies at the End of the 17th Century - Díaz Blanco, José Manuel; Hernández Rodríguez, Alfonso J. (Revista Complutense de Historia de América, 2022)
This paper tries to show how an accidental fact such as the death of a merchant can help us to better understand commercial enterprises in the 17th century Spanish Monarchy, since it provides us with rare private information to be connected with the most usual notarial and administrative documentation. We study the case of Bernardo Clemente Príncipe, which proves that, despite of the innovative arbitrista thought, colonial trade tended to maintain traditional ways of working. In our opinion, the conservative nature of the business micro-structures was consistent with that of the general macro-structure of Spanish trade system.